Profile of Individuals with Parkson's disease performing dance: Coggnitive dysfunction and quality of life - Bento B.M. (2019)
© 2019 Editora Cientifica Nacional Ltda. All rights reserved.Objective: Investigate the relationship between cognitive dysfunction, symptomatology and quality of life of individuals with Parkinson's disease practicing dance classes. Methods: The cross-sectional study consisted of 28 individuals with a mean age of 67.42 ± 10.21 years diagnosed with Parkinson's disease, who performed partner dance twice a week for 50 minutes. A questionnaire was used as an interview divided into five parts: a) Personal identification; b) Scale of Hoehn and Yahr; c) Unified Parkinson's Disease Assessment Scale (UPDRS); d) PDQ-39 Brazilian version; e) Montreal Cognitive Assessment (MoCA). Results: The mean MoCA for individuals with Parkinson's disease in this study was 21.6 ± 4.5, indicating the presence of dementias that may compromise the cognition of these individuals. There was a negative association between MoCA and symptomatology in motor exploration (UPDRSIII) with p = 0.042. There was also a negative association between MoCA and Quality of Life (PDQ-39) in mobility, daily, stigma and communication (p = 0.049, 0.050, 0.033 and 0.035), respectively. Conclusion: Cognitive deficits may present significance in motor exploration and quality of life factors such as mobility, daily communication and stigma.